2003
DOI: 10.1111/j.1365-2591.2003.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of intracanal medicaments to postoperative pain in endodontics

Abstract: Under the conditions of this study, painful teeth with acute apical periodontitis that had been dressed with Ledermix paste gave rise to less pain than that experienced by patients who had a dressing of calcium hydroxide or no dressing at all. Ledermix is an effective intracanal medicament for the control of postoperative pain associated with acute apical periodontitis, with a rapid onset of pain reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
101
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 23 publications
11
101
0
4
Order By: Relevance
“…Therefore, we decided to use alternative intracanal medicaments in our study (Ledermix and TAP). Ledermix was reported an effective intracanal medicament for the control of postoperative pain associated with acute apical periodontitis [23]. TAP may also be a good alternative intracanal medicament with regard to its antibacterial activities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we decided to use alternative intracanal medicaments in our study (Ledermix and TAP). Ledermix was reported an effective intracanal medicament for the control of postoperative pain associated with acute apical periodontitis [23]. TAP may also be a good alternative intracanal medicament with regard to its antibacterial activities.…”
Section: Discussionmentioning
confidence: 99%
“…121,122 Ledermix has been shown to effectively reduce the incidence of postoperative pain in endodontics. 123 However, the superiority of Ledermix over calcium hydroxide in reducing the incidence of postoperative pain associated with acute apical periodontitis is controversial. Ehrmann et al 123 reported superior results with Ledermix over calcium hydroxide in reducing postoperative pain, whereas Fava 124 found no difference between the 2 medicaments in reducing postoperative pain.…”
Section: Antibiotic Preparationsmentioning
confidence: 99%
“…123 However, the superiority of Ledermix over calcium hydroxide in reducing the incidence of postoperative pain associated with acute apical periodontitis is controversial. Ehrmann et al 123 reported superior results with Ledermix over calcium hydroxide in reducing postoperative pain, whereas Fava 124 found no difference between the 2 medicaments in reducing postoperative pain. The control of postoperative pain and inflammation attributable to the use of Ledermix appear to be more likely related to the anti-inflammatory effects of corticosteroid rather than its antibacterial effects.…”
Section: Antibiotic Preparationsmentioning
confidence: 99%
“…14 Root canal treatments are generally finished in a single session, but, especially in very painfully acute apical periodontitis or abscesses, treatment of a root resorption due to trauma, total elimination of the microorganisms from the root canal with root canal preparation and irrigation is impossible, root canal treatment should be finished in the other session after using root canal medicaments. 4,5,21 The effect of long time and short time usage of Ca(OH) 2 on the root fracture has been studied in the literature and the results of these studies are controversial. 10,14,15,22,23 Batur et al 10 indicated that long-term Ca(OH) 2 treatment could significantly reduce the fracture resistance of the teeth.…”
Section: Discussionmentioning
confidence: 99%